2013
DOI: 10.1039/c3cc38952a
|View full text |Cite
|
Sign up to set email alerts
|

Measuring protein reduction potentials using 15N HSQC NMR spectroscopy

Abstract: NMR spectroscopy was used to measure reduction potentials of four redox proteins by following multiple 15N HSQC protein resonances across a titration series using mixtures of oxidised and reduced glutathione. Results for PDI a, PDI ab and DsbA agree with the literature and our result for ERp18 confirms this protein as an oxidoreductase of comparable or greater reducing strength than PDI a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…27 Further, the synovial fluid of rheumatoid arthritis patients has been shown to be highly oxidizing relative to that of a non-arthritic control group. 43,44 A significant body of literature suggests that when overexpressed at sites of inflammation, 16 MIF can endure large swings in environmental redox potential, consistent with our determination of the MIF redox potential in vitro using solution NMR 45,46 (Figure S12, midpoint 𝐸 " # = -215 ± 5 mV, near normal physiological range). NMR spin relaxation studies show redox-dependent modulation of local flexibility in MIF, with motion observed on multiple timescales.…”
Section: Discussionsupporting
confidence: 84%
“…27 Further, the synovial fluid of rheumatoid arthritis patients has been shown to be highly oxidizing relative to that of a non-arthritic control group. 43,44 A significant body of literature suggests that when overexpressed at sites of inflammation, 16 MIF can endure large swings in environmental redox potential, consistent with our determination of the MIF redox potential in vitro using solution NMR 45,46 (Figure S12, midpoint 𝐸 " # = -215 ± 5 mV, near normal physiological range). NMR spin relaxation studies show redox-dependent modulation of local flexibility in MIF, with motion observed on multiple timescales.…”
Section: Discussionsupporting
confidence: 84%
“…27 Further, the synovial fluid of rheumatoid arthritis patients has been shown to be highly oxidizing relative to that of a non-arthritic control group. 43,44 A significant body of literature suggests that when overexpressed at sites of inflammation, 16 MIF can endure large swings in environmental redox potential, consistent with our determination of the MIF redox potential in vitro using solution NMR 45,46 (Figure S12, midpoint ! " = -215 ± 5 mV, near normal physiological range).…”
Section: Discussionsupporting
confidence: 75%
“…If the reaction was solely determined by the active site chemistries then the reaction should proceed in both directions until equilibrium is reached. As their calculated redox potentials are quite similar [ 15 , 39 ], there must be an alternative explanation. NMR studies have shown that the oxidized and reduced states of ERp18 have chemical shift differences between residues in and around the active-site disulfide, consistent with different conformational states [ 40 ].…”
Section: Discussionmentioning
confidence: 99%